Preferences and the level of satisfaction from the provision of insurance services in activity of the LGUs on a municipal level in Podkarpackie voivodship - Tomasz Skica; Jacek Rodzinka (e-Finanse: Financial Internet Quarterly, 2012)
The article is based on the results of author's study survey conducted on a representative sample of municipalities of Podkarpackie voivodship. Based on the results of research, the article will present both the current state of insurance in local government units (LGUs) of the municipal level, as well as the associated changes directly affecting the functioning of the insurance business in LGUs. The primary objective of this paper is to determine the procedures for concluding the insurance in LGUs, and also defining the types of insurance most often executed by these entities, and indication of the intermediaries, whose services are most commonly used by examined LGUs.
Keywords: H7; H72; G22; 330; insurance; local government; satisfaction with insurance services; insurance brokerage; Versicherung; Versicherungsvermittlung; Kommunalverwaltung; Zufriedenheit; Polen